Morphological assimilation of borrowed terminology (on the example of terminological units, borrowed from French) - Kaneeva Anna Vitalievna (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2015)
The study of morphological assimilation is an important and mandatory problem as far as the native speaker media will be comfortable using the term of the borrowing language in the flow of speech, without considering the specific grammatical forms, largely determines its subsequent semantic assimilation, its incorporation into a particular terminology system. The analysis clearly shows the place of French borrowings in the morphological system of the Russian language, helps to identify the most significant differences between the structures of the two languages. At the same time it suggests that many French terminology borrowings morphologically assimilated fairly well, there were some groups in the Russian language, which transformed morphologically French elements falling into Russian. This makes borrowings more smooth, and loan word, provided that it actually meets the needs of the language - receptor in the host language adapts quickly and easily absorbed by native speakers